Ball with hair: modular functionalization of highly stable G-quadruplex DNA nano-scaffolds through N2-guanine modification - Lech, Christopher Jacques (2017)
Functionalized nanoparticles have seen valuable applications, particularly in the delivery of therapeutic and diagnostic agents in biological systems. However, the manufacturing of such nano-scale systems with the consistency required for biological application can be challenging, as variation in size and shape have large influences in nanoparticle behavior in vivo. We report on the development of a versatile nano-scaffold based on the modular functionalization of a DNA G-quadruplex. DNA sequences are functionalized in a modular fashion using well-established phosphoramidite chemical synthesis with nucleotides containing modification of the amino (N2) position of the guanine base. In physiological conditions, these sequences fold into well-defined G-quadruplex structures. The resulting DNA nano-scaffolds are thermally stable, consistent in size, and functionalized in a manner that allows for control over the density and relative orientation of functional chemistries on the nano-scaffold surface. Various chemistries including small modifications (N2-methyl-guanine), bulky aromatic modifications (N2-benzyl-guanine), and long chain-like modifications (N2-6-amino-hexyl-guanine) are tested and are found to be generally compatible with G-quadruplex formation. Furthermore, these modifications stabilize the G-quadruplex scaffold by 2.0–13.3 °C per modification in the melting temperature, with concurrent modifications producing extremely stable nano-scaffolds. We demonstrate the potential of this approach by functionalizing nano-scaffolds for use within the biotin–avidin conjugation approach.